Letter - Mannin, Ethel, 1900-1984
026-0107-001 Ethel Mannin Oak Cottage. Burghley Road. London. SW19 May 5th 1939 Dear Mr. Tewson, I write to you on my private notepaper, but I write nevertheless as Secretary and Treasurer of the English Section of the S.I.A. I write on this paper as I am not often at Frith St, and it is more convenient if you write to me here at my home address. I did not reply immediately to your letter of the 27th April as I wished first of all to convey the contents of your letter to the members of the C.N.T. Committee who wrote to you. I did so this afternoon through the translation of a Spanish-speaking friend. It is not, however, for me to make any comment either on your letter or on the reaction of these Spanish workers, as the S.I.A. is a non-political organisation. The reason that S.I.A. notepaper was used is that these refugees are guests of the S.I.A. and the stationery is at their disposal for letter-writing; they did not write in the name of the S.I.A. but of the C.N.T. and they can hardly be expected to accept a reply at second-hand through another organisation. It is discourteous to say the least of it! Sincerely, Ethel Mannin. 292/946/26/107